The Importance of Employee Trust as a Mediating Job Satisfaction, Employee Relations and Employee Performance - Basuki, Haikal basiswanto; Elmi, Farida (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose – The aim of the study sought to ascertain the impact of employee relations and job satisfaction. Relations with mediation of Employee Trust on employee performance at the delivery service provider company PT TAB in Indonesia. Methodology/approach – These studies employ quantitative descriptive methods. Using a quota sampling type with a non-probability sampling technique, there are 203 couriers at DKI Jakarta who have been employed for over a year. SEM-PLS data analysis with the SmartPLS 3.2.9 program. Findings – According to research, job happiness and employee relations have a favorable and strong direct relationship to employee performance, whereas employee trust has no bearing. Another conclusion was that there was no evidence for an indirect association between work satisfaction and employee relations on employee performance. Novelty/value – It is recommended that the company maintain and maintain the current svstem and promotions and consider reviewing matters related to the distribution of information and policies within the company and continue to consider the recruitment and training system to improve the capabilities of couriers at PT TAB.